Pertautan Epistemologi Bayani dan Pendidikan Islam Masa Keemasan - Mahmud Arif (Al-Jami'ah Research Centre, 2002)
Historically, the current Islamic thought is essentially a continuation of the result of Islamic thought theorizing that peaked in the Golden ages (III - V H). As a consequence of bayaniyyun domination the product of Islamic thought in the Golden ages has succeeded to build an image that Islamic Arabic thought inherited by us currently is nothing but an